2018
DOI: 10.1111/ppa.12910
|View full text |Cite
|
Sign up to set email alerts
|

Anther smut disease caused by Microbotryum on berry campion Silene baccifera: endemic pathogen or host shift?

Abstract: This research investigated whether anther smut disease caused by Microbotryum violaceum agg. on Silene baccifera in Europe is caused by a host‐specific lineage, or if it represents a host shift of the pathogen from a related species. Characterization of ITS sequences of anther smut from S. baccifera confirmed their strong similarity to the pathogen endemic on Silene latifolia. Cross‐inoculation studies showed that S. baccifera was susceptible to anther smut isolates from S. latifolia, S. dioica and S. vulgaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…2008; Tyson et al. 2018), there has been little evidence to suggest a true generalist species in Silene that is actively maintained on two or more hosts. Indeed, patterns of host‐specificity among Silene ‐infecting Microbotryum are present even in communities with sympatric host species (Van Putten et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2008; Tyson et al. 2018), there has been little evidence to suggest a true generalist species in Silene that is actively maintained on two or more hosts. Indeed, patterns of host‐specificity among Silene ‐infecting Microbotryum are present even in communities with sympatric host species (Van Putten et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results with anther-smut fungi of Dianthus differ from patterns of host specificity of Microbotryum on host species in the genus Silene where phylogeographic studies have shown that most species of Microbotryum are specialized to a single host species (Lutz et al 2005;Le Gac et al 2007). Although host shifts can and do occur between closely related species (Antonovics et al 2002;Refrégier et al 2008;Tyson et al 2018), there has been little evidence to suggest a true generalist species in Silene that is actively maintained on two or more hosts. Indeed, patterns of host-specificity among Silene-infecting Microbotryum are present even in communities with sympatric host species (Van Putten et al 2005;Gladieux et al 2010;Hood et al 2019) and overlapping floral phenologies (Tang et al 2019).…”
Section: Variation In Pathogen Host Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the fungi formerly grouped under the Microbotryum violaceum epithet represent a large species complex, consisting of many independent lineages, each specific (i.e., endemic) to only one or a very small number of host species (Kemler et al, ; Le Gac et al, ; Lutz et al, ; Piątek, Lutz, & Kemler, ; de Vienne, Hood, & Giraud, ). However, in marked contrast to the strong host specificity generally seen in those phylogenetic studies, several instances of cross‐species disease transmission have been observed in nature (Antonovics et al, ; Gladieux et al, ; López‐Villavicencio et al, ; Refrégier et al, ; Tyson, Antonovics, & Bruns, ). Cross‐inoculations under experimental conditions further support the potential for host‐shifts in some nonendemic host–pathogen combinations (Biere & Honders, ; Van Putten, Biere, & Damme, ; Shykoff et al, ; Sloan, Giraud, & Hood, ; de Vienne et al, ).…”
Section: Introductionmentioning
confidence: 97%